The Influence of Financial Accounting Learning Quality on Financial Literacy and its Impact on Financial Self-Efficacy - Dewi, Mustika; Makhdalena, Makhdalena; Gimin, Gimin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
This paper documents the influence of the quality of financial accounting learning on financial literacy and its impact on financial self-efficacy. The research uses quantitative descriptive methods through simple linear regression analysis techniques. The research was carried out at the Vocational School of Labor under FKIP, Riau University in the Accounting and Finance Skills Department Program. The population used in this research were students with competency skills in accounting and financial institutions, namely, classes XI and XII in the academic year 2021/2022, all of whom were 90 students studied (census). The research results show that the quality of financial accounting learning influences the financial literacy of students at the Vocational School of Labor under the guidance of FKIP, Riau University. Financial literacy influences students' financial self-efficacy. Quality learning will help in understanding, assessing, and acting in managing students' finances and financial self-efficacy